2001
DOI: 10.1002/1532-2890(2001)9999:9999<::aid-asi1079>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

A noninformetric analysis of the relationship between citation age and journal productivity

Abstract: A problem, raised by Wallace (JASIS, 37, 136–145, 1986), on the relation between the journal's median citation age and its number of articles is studied. Leaving open the problem as such, we give a statistical explanation of this relationship, when replacing “median” by “mean” in Wallace's problem. The cloud of points, found by Wallace, is explained in this sense that the points are scattered over the area in first quadrant, limited by a curve of the form where E is a constant. This curve is obtained by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the second class, the nodes in the citation graph represent collections. Collections may be journals (e.g., [16], [4], [28], [15], [27], [18], [3]), conferences (e.g., [5]), or even authors. The weighted edges in the citation graph represent the total number of citations made from one collection to another.…”
Section: Related Workmentioning
confidence: 99%
“…In the second class, the nodes in the citation graph represent collections. Collections may be journals (e.g., [16], [4], [28], [15], [27], [18], [3]), conferences (e.g., [5]), or even authors. The weighted edges in the citation graph represent the total number of citations made from one collection to another.…”
Section: Related Workmentioning
confidence: 99%
“…Temporal locality has been studied for many years in citation analysis (see e.g., [9,11])-it is well-known that a scientific paper gets the majority of its citations soon after it is published and as time passes, receives fewer citations. Amitay et al [1] have also identified aspects of temporal locality in Web domains, showing that incorporating hyperlink timestamps into link-based page-ranking algorithms can improve retrieval accuracy.…”
Section: Background and Related Workmentioning
confidence: 99%
“…It has been shown that citations of journal articles behave in a consistent manner. In general, the more time passes, the less citatihons a paper receives (Egghe, 2001; Garfield, 1998). In fact, a journal will be considered more prominent the higher its citation half‐life is (i.e., how old in years most of the papers currently cited are in the literature that were previously published in this journal).…”
Section: Introductionmentioning
confidence: 99%